THE RELATIONSHIP BETWEEN LENGTH OF SENTENCE AND LEVELS OF ANXIETY AND DEPRESSION AMONG INMATES AT THE RUTAN KELAS IIB TRENGGALEK - Yohana Christy; Syeikhu Alfa Ridho (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Mental health disorders, particularly anxiety and depression, are common concerns among inmates during incarceration. This study aimed to examine the association between sentence length and levels of anxiety and depression among inmates at Rutan Kelas IIB Trenggalek. This quantitative study employed an analytic correlational design with a cross-sectional approach. The population included all inmates at Rutan Kelas IIB Trenggalek, with a total sample of 73 respondents selected through purposive sampling based on predefined inclusion criteria. Anxiety and depression were assessed using the Patient Health Questionnaire-4 (PHQ-4), while sentence length data were obtained from institutional administrative records. Data were analyzed using Spearman’s rank correlation test with a significance level of p < 0.05. The results showed that the majority of inmates screened negative for anxiety and depression symptoms. No significant association was found between sentence length and levels of anxiety or depression. These findings suggest that sentence length is not significantly related to anxiety or depression among inmates. Nevertheless, routine and continuous mental health screening remains necessary for early detection of psychological symptoms in the detention center setting.